2016
DOI: 10.3889/oamjms.2016.045
|View full text |Cite
|
Sign up to set email alerts
|

Are Dietary Intakes Related to Obesity in Children?

Abstract: AIM:The purpose of this study was to report obesity status and identify any dietary substances that may be related to obesity in healthy school children from Northern Greece.METHODS:Four hundred and twenty-five (n = 425) children were randomly selected to participate in the study. A 24-h recall of three days (two weekdays and one weekend day) was used to analyze the dietary data of the subjects.RESULTS:Out of 425 subjects, 146 (34.3%) of them were found to be overweight and obese. Energy, protein, carbohydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
8
1
Order By: Relevance
“…9 This relationship may explain why researchers in a previous study reported no significant association between energy intake and body composition while others found that energy and carbohydrate intake were significantly (P <0.05) associated with children's BMI. 23,24 The current study also found that total grain intake per day and whole grain or other grain-intake frequency had no significant relationship with BMI z-scores. Different influences of whole grains and refined grains on obesity have been documented previously in the literature.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…9 This relationship may explain why researchers in a previous study reported no significant association between energy intake and body composition while others found that energy and carbohydrate intake were significantly (P <0.05) associated with children's BMI. 23,24 The current study also found that total grain intake per day and whole grain or other grain-intake frequency had no significant relationship with BMI z-scores. Different influences of whole grains and refined grains on obesity have been documented previously in the literature.…”
Section: Discussioncontrasting
confidence: 43%
“… 9 This relationship may explain why researchers in a previous study reported no significant association between energy intake and body composition while others found that energy and carbohydrate intake were significantly ( P <0.05) associated with children’s BMI. 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…Adequate nutrition during this period is of great importance. A number of studies has revealed that inappropriate nutrition in childhood is related to both the occurrence of diseases in youth [ 1 ] and the risks of developing obesity, cardiovascular diseases, and cancer in adulthood [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of the study was that physical activity was not captured and thus activity levels could not be adjusted for in this analysis. Although subjective measures of dietary data collection using a standardized protocol were used, the likelihood of underreporting and/or misreporting is possible as reported in other studies (43,44). With the study being cross-sectional, conclusions on cause-and-effect relationships and the direction of the associations observed cannot be made.…”
Section: Resultsmentioning
confidence: 99%